Pertanggungjawaban Aspek Hukum Ketenagakerjaan yang Dilakukan oleh Karyawan Terhadap Perusahaan (Studi Kasus Putusan No. 42/PID.B/2025/PN Banjar) - Nur Rizkiah Hasanah; Hammamtio; Atik Winanti (CV Rewang Rencang, 2025)
The company has a legal and social obligation to treat employees fairly by fulfilling the normative rights inherent in the employment relationship. This responsibility can be realized through providing wages that are appropriate to the workload and time, providing social security such as health insurance and other benefits, and adjusting wages based on the inflation rate and the provisions of applicable laws and regulations. In the Banjar District Court Decision Number: 42 / Pid.B / 2025 / PN Bjr, the defendant's actions caused the Tunas Artha Mandiri Cooperative to suffer a loss of Rp. 87,294,000.00. This was done by creating fictitious data, marking up loans, and not paying member installments. As a result, the defendant was found guilty of committing the Crime of Embezzlement with his inherent position in accordance with Article 374 of the Criminal Code. In addition, the employment agreement between the two parties can be canceled because it does not comply with the valid conditions of the agreement as regulated in Article 1320 of the Civil Code, directly revokes the Rights and Obligations of both parties as regulated in Law Number 11 of 2020 concerning Job Creation.